Coding grammatical signals in Western Tamang: a typological perspective - Regmi, Dan Raj (Nepalese Linguistics, 2019)
Western Tamang differs from Eastern Tamang while coding grammatical signals by different morphosyntactic devices especially at propositional information level. Both dialects almost equally share most of the common structural features of Bodish group. However, dialect specific differences have to be compared from a typological perspective for practical implications in Tamang.